Mechanisms of communication between mitochondria and lysosomes. (October 2016) - Raimundo, Nuno; Fernández-Mosquera, Lorena; Yambire, King Faisal; Diogo, Cátia V.
Highlights: Mutations in genes encoding for mitochondrial or lysosomal proteins lead to severe diseases. Mitochondrial malfunction triggers increase in number of autophagosomes. Mitochondrial stress leads to lysosomal dysfunction and accumulation of autophagy intermediates. Mitochondrial stress triggers lysosomal biogenesis in dividing cells. Lysosomal defects trigger mitochondrial perturbations. Mitochondria and lysosomes show interdependence, as dysfunction of one results in perturbation of the other. Abstract: Mitochondria and lysosomes have long been studied in the context of their classic functions: energy factory and recycle bin, respectively. In the last twenty years, it became evident that these organelles are much more than simple industrial units, and are indeed in charge of many of cellular processes. Both mitochondria and lysosomes are now recognized as far-reaching signaling platforms, regulating many key aspects of cell and tissue physiology. It has furthermore become clear that mitochondria and lysosomes impact each other. The mechanisms underlying the cross-talk between these organelles are only now starting to be addressed. In this review, we briefly summarize how mitochondria, lysosomes and the lysosome-related process of autophagy affect each other in physiology and pathology.